Competitive posture of selected medical school deans - Hernando, Harivelle Charmaine T.; De Guzman, Ligaya S.; Zalamea, Evangeline (2015)
The competitive posture of the Medical School Dean, as perceived by the Deans themselves, the faculty, and the students, was studied by determining the level of effectiveness in terms of three competencies (academic, administrative, and leadership) and seven key areas (student services, physical plant/resources, teaching-learning aspect, research, social relations, staff management, and student management). The strengths, weaknesses, opportunities, and threats on the Dean were also identified.

Thy systems model (input - process - output) was the framework for this descriptive study utilizing the mixed method (quantitative data - questionnaire; qualitative data - interviews, school records), with respondents consisting of 3 deans, 384 faculty, and 646 students from 3 selected medical schools in Metro Manila.

The level of effectiveness of the Dean ranged from good to excellent in terms of the three competencies and seven key areas, with several strengths and opportunities to build upon, upgrade, and develop oneself and the institution he/she represents.
Keywords: Medical college administrators -- Rating of; Strategic planning